Research on Network Data Algorithm Based on Association Rules - Rui Wang (International Journal of Informatics and Information Systems, 2023)
The network data algorithm on account of association can effectively describe the development process of historical data and predict the development trend of data. Draw support from the corresponding data algorithm to ameliorate the mining efficiency and execution efficiency of association, more users pay more attention to the rules, so it has important research and utilization value. On account of this, this paper first analyses the concept and mining process of data association, then studies the mining algorithm of data association, and finally gives the structure and utilization effect of cyber data algorithm on account of association.